2011
DOI: 10.1177/1059840511418670
|View full text |Cite
|
Sign up to set email alerts
|

Asian Student Depression in American High Schools

Abstract: There are inconsistent findings about depression in Asians. This study examined risk factors for depression in Asian and Caucasian adolescents. Stratified bivariate secondary analyses of risk indicators and depressed mood were performed in this cross-sectional study of high school survey data (9th to 12th grades) from 2,542 students (198 Asian). Asians had a higher prevalence of depressed symptoms, but similar risk factors as Caucasians. Smoking and injury at work were major risk factors for depressed mood amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 27 publications
(35 reference statements)
1
36
0
Order By: Relevance
“…Song et al found that female gender was associated with depressed mood among female Asian high school students, 34 Chen et al and Juang et al found that Chinese adolescent females had higher levels of depressive symptoms than males, 31,35 Javier et al found that Filipino females reported higher levels of depressive symptomology than males, 36 and Williams et al found an association between female gender and depressive symptoms among Japanese American adolescents. 37 …”
Section: Question 1: What Do We Know About Risk and Protective Factormentioning
confidence: 99%
See 2 more Smart Citations
“…Song et al found that female gender was associated with depressed mood among female Asian high school students, 34 Chen et al and Juang et al found that Chinese adolescent females had higher levels of depressive symptoms than males, 31,35 Javier et al found that Filipino females reported higher levels of depressive symptomology than males, 36 and Williams et al found an association between female gender and depressive symptoms among Japanese American adolescents. 37 …”
Section: Question 1: What Do We Know About Risk and Protective Factormentioning
confidence: 99%
“…41 Song et al found that worrying about school failure or grades was associated with depressed mood among Asian high school students. 34 Additionally, Mistry et al found that parental reports of economic stress predicted Chinese adolescents’ depressive symptoms. 42 …”
Section: Question 1: What Do We Know About Risk and Protective Factormentioning
confidence: 99%
See 1 more Smart Citation
“…Empirical research indicates differences in rates of depression between U.S.- and foreign-born persons both within an ethnic group and across ethnic groups (e.g., Alegria et al, 2007; Almeida, Subramanian, Kawachi, & Molnar, 2009; Cheung, Leung, & Cheung, 2011; Song, Ziegler, Arsenault, Fried, & Hacker, 2011; Sumner et al, 2010; Szaflarski et al, 2011; Williams et al 2007). We are aware of only one study that examined college students (Szaflarski et al, 2011).…”
Section: 2 Depression Symptoms Among Us- and Foreign-born Asian mentioning
confidence: 99%
“…Song, Ziegler, Arsenault, and Hacker (2011), in this issue, report a comparison of Asian and Caucasian students' depression and risk factors. Descriptive statistics allow for a comparison of risk between the two groups and logistic regression analysis describes the odds ratio (OR) of one group exhibiting symptoms of risk compared to another.…”
mentioning
confidence: 99%